The Mathematics in Our Hands How Gestures Contribute to Constructing Mathematical Knowledge - Krause, Christina M. (Springer Fachmedien Wiesbaden : Imprint: Springer Spektrum, 2016)
In her empirical study, Christina Krause investigates how gestures can contribute to epistemic processes in social interactions. She expands the traditional speech-based approach to analyzing social processes of constructing mathematical knowledge by employing a multimodal perspective. Adopting a semiotic approach, she takes into account two functions of gestures as signs used by the participants of the social interaction: the representational function concerns the ways in which gestures take part in referring to a mathematical object in processes of knowledge construction and the epistemic function relates to the ways in which they can contribute to the performance of collective epistemic actions. The results of this study reveal that gestures influence the epistemic process significantly more than previously thought and indicate factors underlying this influence. Contents On the Role of Gestures in Learning Mathematics A Semiotic Approach and Perspectives on Learning Extended Methods and Methodology Results on the Representational and the Epistemic Functions of Gestures Towards the Role of Gestures: A Comparison Reflections, Synopsis, Perspectives Target Groups Scientists and teachers in mathematics education and gestures studies The Author Christina Marie Krause earned her PhD at the University of Bremen. She currently holds a postdoctoral position at the Mathematics Education working group of the University of Duisburg-Essen and works as a researcher and lecturer. .